God in the thought of buddha and Confucius - Kajour, Antar (International Journal of Psychosocial Rehabilitation, 2022)
This article aims to show that Buddha and Confucius were not atheists or rejecters of religion, and that what was rumored or quoted about them is not based on strong evidence and compelling argument. It is just lies and sayings without arguments. And that Buddhism and Confucianism are religions or religious reform movements, which came in order to bring salvation and happiness to humanity. This article also discusses the evidence for each group, and the arguments they hold, whether they are portrait or rational. Finally, this paper proposes to encourage Muslim researchers to address this subject, with more research and study, because this contributes to serving Islam and spreading its call.